Veni Domine - Christmas at the Sistine Chapel Sistine Chapel Choir - Josquin des Prez -1521; Palestrina, Giovanni Pierluigi da 1525?-1594; Nanino, Giovanni Maria 1543 or 1544-1607; Palestrina, Giovanni Pierluigi da 1525?-1594; Victoria, Tomás Luis de approximately 1548-1611; Palestrina, Giovanni Pierluigi da 1525?-1594; Victoria, Tomás Luis de approximately 1548-1611; Clemens non Papa, Jacobus approximately 1510-approximately 1555; Palestrina, Giovanni Pierluigi da 1525?-1594; Palestrina, Giovanni Pierluigi da 1525?-1594 ([publisher not identified], 2017)
Join the talented young singers of the acclaimed Sistine Chapel choir--one of the oldest choirs in the world!--for an enthralling concert of Advent and Christmas-themed polyphonic chefs-d'uvre from the Vatican Library's vault! Filmed in the legendary architectural and artistic masterpiece of a room that gave the choir its name, highlights from the performance include never-before-recorded works by Renaissance masters like Giovanni Pierluigi da Palestrina, Guillaume Dufay, and Gregorio Allegri! A truly out-of-the-ordinary Christmas celebration! Photo: Sistine Chapel Choir © Stefano Prospero Spataro
Keywords: Motets; concert; Sacred music; Filmed performances; Internet videos